Urogenital colonization and pathogenicity of E. Coli in the vaginal microbiota during pregnancy - Nassim Boutouchent; Thi Ngoc Anh Vu; Luce Landraud; Sean P. Kennedy (Scientific Reports)
Abstract This study explores the role of the vaginal microbiota (VM) in the pathophysiology of asymptomatic bacteriuria (ASB) in a cohort of 1,553 pregnant women. Worldwide, E. coli remains the most common etiological agent of bacteriuria during pregnancy and also a major causative agent of newborn infections. A healthy VM is typically characterized by low diversity and is dominated by lactic acid-producing species, notably those from the Lactobacillus genus. Our results point to decreases in Lactobacillus spp associated with an increase of gut-microbiota-associated species from the Enterobacterales order. Escherichia coli exhibited the most pronounced increase in abundance within the VM during bacteriuria and was notably associated with ASB. Molecular typing and antimicrobial resistance characterization of 72 metagenome assembled E. coli genomes (MAGs) from these pregnant women revealed a genomic signature of extraintestinal pathogenic E. coli (“ExPEC”) strains, which are involved in various extraintestinal infections such as urinary tract infections, newborn infections and bacteremia. Microbial diversity within the vaginal samples from which an E. coli MAG was obtained showed a substantial variation, primarily marked by a decrease in abundance of Lactobacillus species. Overall, our study shows how disruption in key bacterial group within the VM can disrupt its stability, potentially leading to the colonization by opportunistic pathogens.